Analysis of energy systems for poly-generation using optimization modelling: the optimization process strategies and the formalization of an innovative multi-objective optimization model - Fragiacomo Petronilla; Lucarelli Giuseppe; Florio Gaetano (E3S Web of Conferences, 2021)
The purpose of this paper is to describe the numerical modelling processes and optimization strategies of energy systems and to formalize an innovative optimization model for poly-generation systems. The model uses a multi-objective optimization approach, by means of three optimization functions: one of an economic nature, one technical and one relating to polluting emissions. The constraint equations of the problem, the boundary conditions and the input values, as well as some dimensionless parameters are described. In addition to a complete approach, the article proposes innovative aspects based on the studies in the literature, both from a technological and economic-regulatory standpoint. For each proposed innovation, an analysis of how this can influence the optimization model is presented and various types of optimization models have been evaluated, depending on the complexity of the physical system and the consequent numeric modelling.